Correlation Analysis of Gut Microbiota and Serum Metabolome With Porphyromonas gingivalis-Induced Metabolic Disorders - Dong, ZhengJie; Lv, WanQi; Zhang, ChenYang; Chen, Si (Frontiers in Cellular and Infection Microbiology, 2022)
Periodontitis has been demonstrated to increase the risk of metabolic syndrome (MetS), but the underlying mechanism remains unclear. Recent studies have indicated periodontopathic bacteria such as Porphyromonas gingivalis could induce gut microbiota (GM) dysbiosis and aggravate metabolic disorders. However, the effects of microbial metabolites have barely been evaluated. Here, we investigated the alteration of serum metabolome with P. gingivalis-induced metabolic disorders, and explored the correlations of GM and serum metabolites. In this study, we orally administered P. gingivalis ATCC33277 to C57BL/6 mice and performed metagenomic sequencing and untargeted metabolomics with fecal samples and serum collection. In vivo experiments showed a higher proportion of fat mass and worse glucose tolerance in P. gingivalis-administered mice, accompanied with an increase of adipose inflammation and gut permeability, which was similar to HFD-induced obese mice. Metagenomic sequencing indicated a compositional and functional alteration of GM. Untargeted metabolomics revealed an alteration of metabolites in P. gingivalis-administered mice, and most of them were engaged in metabolic pathways, such as tryptophan metabolism and choline metabolism. Correlation analysis between GM and serum metabolome indicated strong relativity with P. gingivalis administration. These results demonstrated some specific microbiota-derived metabolites in the pathogenesis of P. gingivalis-induced metabolic disorders, providing promising targets for the development of novel treatment strategies for MetS.